Pemetaan Persepsi dan Sikap Guru Matematika SMA di Banda Aceh Dalam Menghadapi Persaingan Masyarakat Ekonomi ASEAN (MEA) - Fithri Angelia Permana; Khairul Asri (Jurnal Dedikasi Pendidikan, 2018)
Along with technological advances, the Government also made an agreement on the enactment of a single market in Asia known as the ASEAN Economic Community (MEA). In the face of MEA, teachers must have more ability in order to compete in the field of work and also able to produce students who are able to compete. This task is not light for the Government, especially for the teacher himself. For that purpose this research is done so that teacher have insight about what, who, why, how, when, and where the MEA. Especially to face the MEA that has been effective starting January 1, 2016 and then, there is no specific information about the perception and attitudes of teachers towards the implementation of the MEA. The importance of knowing the perceptions and attitudes of high school mathematics teachers in Banda Aceh is due to the perception and attitude of the mind-set that can lead to one's actions and treatment. Mapping perceptions and attitudes of high school mathematics teachers in Banda Aceh became a necessity for the program to be run by the Government to assist high school mathematics teachers in Banda Aceh appropriate and on target. After the research, the results obtained in the form of mapping the perception and attitude of high school math teachers in Banda Aceh. In general, the perception and attitude of the mathematics teacher in Banda Aceh is that the MEA never existed, the MEA is not something that needs attention, and does not want to know about the applicable MEA competition.